Relationship between Human Resource Management (HRM) practices and employability among Universiti Teknologi MARA Sports Graduates / Nur Syazwani Zulaikha Safwan - Safwan, Nur Syazwani Zulaikha (2022)
Currently, turnover intention has become an issue debated in Malaysia. It has become a worldwide issue due to the dissatisfaction with Human Resource Management (HRM) practices and employability skills of an individual in the organization. The objective of this study was to explore the level of HRM practices and employability as well as examining the relationship between HRM practices and employability among UiTM sports graduates. Besides, 370 UiTM sports graduates were used in carrying out this study. The data has been obtained through a questionnaire consisting of 26 items divided into five practices of HRM; recruitment and selection, training and development, reward, performance appraisal and participation and communication. Meanwhile, 20 items were used to measure employability. The data were analyzed using Pearson correlation. The findings show all practices of HRM were at a moderate level and the graduates’ employability was at a high level. Besides, there is also a significant and moderate positive relationship between five practices of HRM and employability among UiTM sports graduates (p = .00 < .05). Therefore, understanding about HRM practices and employability enable graduates and organizations prepared with relevant practices and skills needed in achieving organizational goals.